Behaviour of subarctic red-backed voles ( Clethrionomys gapperi athabascae ) - Mihok, Steve (Canadian Journal of Zoology, 1976)
Interactions between pairs of red-backed voles were observed in a neutral observation arena in the summer of 1975 at Heart Lake. Northwest Territories, Canada. Twenty–one behaviours were recorded for each vole and were simplified to six factors of behaviour: amicable, defensive, aggressive, avoidance, subordinate, and fighting. The behaviour of one vole towards another in a trial was classified into defensive, avoidance, amicable, and aggressive types by unweighted pair group method (UPGM) cluster analysis. It was possible to partially predict behaviour on the basis of individual parameters such as: sex, age, and reproductive condition. The relationship between individuals showed better predictability, although the behaviour of each individual was variable. Male–female encounters were generally amicable with the female being dominant. Female–female encounters were similar to male–male encounters; avoidance, defensive, and aggressive behaviour predominated. Dominant females were generally older or in a later stage of pregnancy. Dominant males did not represent any consistent trends in age, sexual maturity, or weight differences. Mutual avoidance was the most common type of interaction.